Biomechanical insights into the determinants of speed in the fencing lunge - Guan, Y.; Guo, L.; Wu, N.; Zhang, L.; Warburton, D. E. R. (European Journal of Sport Science, 2018)
For fencing, speed of the lunge is considered critical to success. The aim of this study is to investigate determinants of lunge speed based on biomechanics. Ground reaction force (GRF) and three-dimensional kinematic data were collected from 7 elite fencers and 12 intermediate-level fencers performing maximum-effort lunges. The results showed that elite fencers acquired a higher horizontal peak velocity of the centre of gravity (HPV) and concomitantly a higher horizontal peak GRF exerted by rear leg (PGRF) than intermediate-level fencers (P < .01). Studying the affecting factors, elite fencers obtained higher joint peak power, joint peak moment, and range of motion of rear knee than intermediate-level fencers (P < .05) during the lunge, and these parameters were significantly correlated with both HPV and PGRF (P < .05). Both elite and intermediate-level fencers had joint flexion before the extension in forward knee; however, the latter showed greater flexion, higher peak angular velocity and less time for extension compared to the former (P = .05). Our findings suggest that training aimed at enhancing strength and power of rear knee extensors is important for fencers to improve speed of the lunge. Also, increasing the extension of rear knee during the lunge, at the same time decreasing the flexion of the forward knee before extension are positive for lunge performance.